Keeping up with your Friends: Function Foo, Library Bar.DLL, and Work Item 24 - Begel, Andrew; Zimmermann, Tom (Proceedings of Web2SE: First Workshop on Web 2.0 for Software Engineering, 2010)
Development teams who work with others need to be aware of what everyone is doing in order to manage the risk of taking on dependencies. Using newsfeeds of software development activities mined from software repositories, teams can find relevant information to help them make well-informed decisions that affect the success of their endeavors. In this paper, we describe the architecture of a newsfeed system that we are currently building on top of the Codebook software repository mining platform. We discuss the design, construction and aggregation of newsfeeds, and include other important aspects such as summarization, filtering, context, and privacy.